The Frequency of Multidrug-Resistant Tuberculosis Patient who have History of Tuberculosis, HIV, and Diabetes Mellitus at Dr. Soetomo General Academic Hospital - Marsha Zahrani; Rebekah J. Setiabudi; Helmia Hasan; Manik Retno Wahyunitisari (Universitas Airlangga, 2023)
Introduction: The main causes of MDR TB include interperson transmission and TB treatment failure. In addition to TB, HIV and diabetes mellitus may raise the risk of TB MDR. To determine the TB MDR risk factors, it's critical to understand the prevalence of TB MDR patients with TB, HIV, and diabetes mellitus histories.Methods: This study is an observational descriptive study with a retrospective design. The sample for this study was all patients from the TB and MDR-TB polyclinic at Dr. Soetomo General Academic Hospital, Surabaya, in January 2020–December 2020 who met the inclusion criteria. The data obtained were analyzed descriptively.Results: There were 72 patients who met the criteria: there were 26 patients who have a history of TB, 15 patients who only have a history of diabetes mellitus, 2 patients who only have a history of HIV, 27 patients who have a history of TB with diabetes mellitus, and 2 patients who have a history of TB with HIV.Conclusion: The data could support the theory of an association between MDR-TB with TB, HIV, and diabetes mellitus and increase the awareness of primary MDR TB cases with history of HIV and diabetes mellitus.